Analisis Wanprestasi dan Penerapan Klausul Non-Competition dalam Putusan Mahkamah Agung Nomor 1785 K/Pdt/2023 - Nabila Alysha; Fitri Rahmadani; Ditia Prabandari; Hana Alicia; Safa Manohara; Dwi Aryanti Ramadhani (Media Hukum Indonesia (MHI), 2026)
This article analyzes the relationship between breach of contract (wanprestasi) and the enforcement of non-competition clauses in employment agreements, using the Supreme Court Decision Number 1785 K/Pdt/2023 as the main reference. The research aims to examine three core aspects: (1) the legal status of post-employment obligations as binding performance, (2) the determination of prohibited actions within non-competition clauses, and (3) the limitation of contractual liability only to parties who expressly bind themselves under the principle of privity of contract. The method used is normative juridical analysis through statutory interpretation, judicial reasoning, and doctrinal review. The study finds that non-competition clauses constitute negative performance that continues to bind workers even after the employment relationship ends, as long as the clause is clearly formulated and mutually agreed upon. The Supreme Court affirms that any form of involvement direct or indirect with a competitor within the agreed period constitutes breach of contract. However, contractual liability cannot be extended to third parties unless they actively participate in the breach. The findings highlight the need for proportionality, clarity of scope, and fairness in enforcing non-competition clauses within Indonesia’s legal framework.